2007
DOI: 10.1002/eji.200636764
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4 depletion enhances host resistance and passive IgA protection against tuberculosis infection in BALB/c mice

Abstract: The influence of Th2 cytokines in tuberculosis has been a matter of dispute. Here we report that IL‐4 has a profound regulatory effect on the infection of BALB/c mice with Mycobacterium tuberculosis. Depletion of IL‐4 with a neutralizing mAb caused only evanescent reduction of lung infection, but when combined with i.n. inoculations of IgA anti‐mycobacterial α‐crystallin mAb and mouse rIFN‐γ, we observed a 40‐fold reduction of the bacterial counts in the lungs at 3 wks following i.n. infection (p<0.001). In ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 55 publications
1
41
0
1
Order By: Relevance
“…Moreover, neutralization of IL-4 and IL-13 in AD skin augmented LL-37 and thereby limited viral infections (81). These findings are supported by murine studies showing that IL-4 depletion in BALB/c mice, which are commonly used to study allergic inflammation, substantially reduced Mycobacterium tuberculosis infections while reconstitution with IL-4 increased bacterial counts to wild-type levels (82). Moreover, another study demonstrated that alveolar macrophages from Paracoccidioides brasiliensis infected IL-4 )/) mice controlled in vitro fungal growth more efficiently than macrophages from wildtype mice and secreted higher levels of nitric oxide.…”
Section: Can Anti-th2 Intervention Strategies Restore Impaired Host Dmentioning
confidence: 80%
“…Moreover, neutralization of IL-4 and IL-13 in AD skin augmented LL-37 and thereby limited viral infections (81). These findings are supported by murine studies showing that IL-4 depletion in BALB/c mice, which are commonly used to study allergic inflammation, substantially reduced Mycobacterium tuberculosis infections while reconstitution with IL-4 increased bacterial counts to wild-type levels (82). Moreover, another study demonstrated that alveolar macrophages from Paracoccidioides brasiliensis infected IL-4 )/) mice controlled in vitro fungal growth more efficiently than macrophages from wildtype mice and secreted higher levels of nitric oxide.…”
Section: Can Anti-th2 Intervention Strategies Restore Impaired Host Dmentioning
confidence: 80%
“…The extent by which the spontaneous post-chemotherapy relapse was prevented has been more profound than the previously reported CIT inhibition of fresh Mtb infection. 16 This could be due to differences between the persister or replicating target organisms. Furthermore, persisters arising rapidly following chemotherapy are apparently resilient to host T cell immunity, unlike the dormant organisms generated following acquired host T cell immunity.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This study has been initiated under the direct influence of our preceding experiments which showed, that (i) passive vaccination with a mouse IgA monoclonal antibody (mAb) against the a-crystallin (Acr) antigen of Mtb together with IFNg reduced the lung infection and pathology in BALB/c mice 15 and (ii) combining this regimen with the inoculation of IL-4 neutralizing antibody was even more protective. 16 The combined immunotherapy regimen composed of IFNg þ IgA þ anti-IL-4 was evaluated in this study for its capacity to reduce the spontaneous relapse of active tuberculous infection following short-term (incomplete) chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In genetically deficient IL-4-/-BALB/c mice, infection in both lungs and spleen was substantially reduced for up to 8 weeks. Reconstitution of IL-4-/-mice with rIL-4 increased bacterial counts to wild-type levels and making mice refractory to protection by IgA/IFN- [65].…”
Section: Studies Performed With Monoclonal Antibodiesmentioning
confidence: 99%